Non-monogamy agreements and safer sex behaviors: The role of perceived sexual self-control. Issue 4 (2nd October 2019) - Rodrigues, David L.; Lopes, Diniz; Conley, Terri D.
ABSTRACT: Attitudes toward condoms and self-control are reliable predictors of consistent condom use. However, safer sex behaviors depend on whether people are single or romantically involved. For the latter, it also depends on whether people are non-consensually non-monogamous (NCNM) or consensually non-monogamous (CNM). A cross-sectional study with 512 Portuguese heterosexual users of the Second Love website (77.0% men; M age  = 37.64, SD  = 7.37; 47.8% romantically involved) examined if attitudes toward condom use were associated with safer sex behaviors – condom use negotiation and condom use frequency – and if this association was mediated by the perception of greater sexual self-control. For single participants we focused on casual partners, and for romantically involved participants we focused on both extradyadic casual partners and the primary partner. Results showed that perceived sexual self-control mediated the association between attitudes and condom use negotiation with casual partners. However, for condom use frequency there was only evidence of mediation for romantically involved (and not single) participants. Lastly, results showed mediations for both safer sex behaviors with the primary partner, but only for CNM (and not NCNM) participants. These findings highlight the importance of sexual self-control and the need to acknowledge relationship agreements.